(3RGO GdeSGaQ (B((3aj GdWH(B)s - (3CHh eMeO GdfjSGHhQj , CMeO Hf EHQGgje, CHh eMeOs
(3ChdgG (B:s
(3hHYO Pdc aEfj fXQJ aj GdJLGQI GdJi CMOKJgG hGdShb GdJi CbeJgG aCdaJ dc (B- (3COGe Gddg YRc hSdGeJc (B- (3cJGHkG LeYJ ajg ef Yjhf eG PcQg CaGVd GdCWHGA s
(3BNQgG (B:s
(3ai UaI VeGO (B: (3hjNHU HOgf GRjJ hGdJTQjL, hjSJYed UaI Ef TGA Gddg s
(3cJHgG cGJH GHf GdMSf GHf CMeO GdbQTj GdYOfGfjs
(3hYdjgG JedcGJ HGSe fGUQ Hf UGdM Hf YeQ heMSf Hf YHOGddg Hf Ydj SfI (B1266 (3g`s
(3hocJHJ CHhGHgG haUhdgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs